2008
DOI: 10.1258/acb.2007.007074
|View full text |Cite
|
Sign up to set email alerts
|

Self-prescribed high-dose vitamin D3: effects on biochemical parameters in two men

Abstract: The lowest observed adverse effect level for vitamin D, said to cause hypercalcaemia in normal adults, is officially 95 mg/day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 10 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…As stored vitamin D gradually returns into the circulation, it is converted into 25(OH)D. The result is that when vitamin D treatment is discontinued, the level of serum 25(OH)D is sustained by the returning phase of the equilibrium between vitamin D in its various body compartments back into the circulation. When supplies of vitamin D are stopped, the serum 25(OH)D declines with a biological half-life of about 2 months [117,118,121]. Even though the half-life of molecules of 25(OH)D per se exhibit a half-life of only 2 weeks [32], the functional half-life of 25(OH)D is 2e3 months.…”
Section: Body Storage Of Vitamin D and Inefficient Conversion To 25(oh)dmentioning
confidence: 99%
See 1 more Smart Citation
“…As stored vitamin D gradually returns into the circulation, it is converted into 25(OH)D. The result is that when vitamin D treatment is discontinued, the level of serum 25(OH)D is sustained by the returning phase of the equilibrium between vitamin D in its various body compartments back into the circulation. When supplies of vitamin D are stopped, the serum 25(OH)D declines with a biological half-life of about 2 months [117,118,121]. Even though the half-life of molecules of 25(OH)D per se exhibit a half-life of only 2 weeks [32], the functional half-life of 25(OH)D is 2e3 months.…”
Section: Body Storage Of Vitamin D and Inefficient Conversion To 25(oh)dmentioning
confidence: 99%
“…Based on clearly published data on calcium through various protocols, ranging from 4 months at 10 000 IU daily, to 15 months at 4000 IU daily to a year of an average intake of 14 000 [54,57,79,137,138], I can conclude on a firm basis of data that vitamin D in doses relevant to nutrition and therapeutics does not raise serum calcium e not even incrementally. That said, we have reported on a patient with multiple sclerosis who was motivated to maximize his serum 25(OH)D; he raised his calcium upon prolonged consumption of 80 000 IU (2000 mg) daily [118], a dose well beyond the realm of this discussion. By now, it should be obvious that the hypercalcemia elicited by Narang et al (138) and which was the basis of the 1997 dietary upper level for vitamin D was essentially a bioassay showing that the vitamin D doses they actually administered were far higher than the 3800 IU daily they thought they had given.…”
Section: Vitamin D Toxicity and Safety Issuesmentioning
confidence: 99%
“…Our patient is interesting because of the unusually long duration of hypervitaminosis D. In previous vitamin D-intoxicated patients, the serum 25(OH)D declined with a half-life of about 2 months after dosage was discontinued [7,8]. The present patient differed further from previously reported cases of vitamin D intoxication, because she also suffered from primary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 49%
“…Her primary hyperparathyroidism was probably latent (with low PTH levels) because of a high 25(OH)D, severe hypercalcemia, and probably by elevated 1,25(OH)2D [9]. Vitamin D2 treatment precipitated hypercalcemia, thereby unmasking her primary hyperparathyroidism; other patients taking such doses (albeit vitamin D3, not D2) did not become hypercalcemic [8].…”
Section: Discussionmentioning
confidence: 97%
“…As with measures of biochemical efficacy, the timing of safety assessments is crucial. The risk of maternal hypercalcemia was low for the doses selected, but would be highest when the circulating concentrations of vitamin D metabolites collectively exceed the capacity of the vitamin D binding protein (Kimball and Vieth, 2008), which would most likely occur within the first 2 weeks after dose administration. Sahu et al (2009) only reported maternal serum calcium concentration at delivery, thus missing the relevant window of exposure.…”
Section: Ps Shettymentioning
confidence: 99%